0501 Development and Initial Evaluation of Web-Based Cognitive Behavioral Therapy for Insomnia "Nitecapp" in Rural Dementia Caregivers: A Mixed-Methods Study. (27th May 2020) - McCrae, C; Curtis, A F; Nair, N; Deroche, C B; Shenker, J; Rowe, M
Abstract: Introduction: Informal caregivers (CGs) of persons with dementia frequently experience insomnia. The time consuming and unpredictable schedule of CGs, and associated emotional/physical exhaustion emphasize the need for brief, easily accessible interventions to treat insomnia. Internet-based behavioral insomnia interventions hold promise, particularly for rural CGs who have limited access to traditional in-person treatments. This study aimed to 1) translate an efficacious 4 session cognitive behavioral therapy for insomnia (CBT-I) to web-based "NiteCAPP" for dementia caregivers, and 2) conduct NiteCAPP usability testing/evaluate acceptability of content and features. Methods: NiteCAPP is an online CBT-I that incorporates guided delivery through weekly therapist moderator feedback. A stepwise approach was implemented in order to explore user needs and validate NiteCAPP content in a focus group of rural dementia caregivers (n=5) and primary care providers (PCPs; n=5). Participants conducted usability testing and provided ratings of program content (1-least favorable to 5-most favorable) regarding ease of use, amount of information, website maintaining interest, adequate font size, videos maintaining interest/easy to understand/helpful. Participants also indicated whether they had at home internet access, method of internet access, and provided open ended feedback on NiteCAPP. Feedback transcripts were compiled and analyzed independently (C.S.M., A.F.C.) through deductive content analysis. Topics mentioned frequently were categorized and merged into common themes during consensus meeting, and NiteCAPP was subsequently adapted. Results: Average ratings for NiteCAPP features were high, ranging from 4.1/5 to 4.7/5 across all items. All participants had access to internet through both phone and computer. No barriers to use identified. Feedback themes were largely positive (e.g., comprehensive written material, promotes independence, excellent visual tools for therapy moderator feedback, good pacing, use of visual contrast). Negative themes for improvement/adaptation included adding font size options, a light/dark mode, tab with all videos, reducing amount of scrolling, adding a glossary of terms. Conclusion: Rural dementia CGs and PCPs evaluated NiteCAPP as easy to use with acceptable features and program content and no barriers to access. Improvement themes were used to adapt NiteCAPP. Next steps are to evaluate feasibility and preliminary efficacy of NiteCAPP in rural dementia CGs with insomnia. Support: none